Trends and Issues in Research on Social Media and Collaborative Learning in PAI Learning from 2018 to 2023: Bibliometric Analysis - Afif Alfiyanto; Dedi Wahyudi; Mailizar; Misbahul Jannah (PT ARRUS Intelektual Indonesia, 2023)
This article aims to identify and analyze trends and problems in research on social media and collaborative learning in Islamic Religious Education (PAI) from 2018 to 2023. The author uses a bibliometric study method using Publish or Perish and bibliometric software. The research results show that 1) RQ1: Distribution of Social Media Research and Collaborative Learning in PAI Learning (2018-2023), namely research authority is focused on social media, which is connected to several themes such as Islamic religious education (PAI), and Islamic education. shows that research orientation on social media topics is used in several studies related to PAI learning and Islamic teaching. However, no one has researched the relationship between social media and collaborative learning in PAI learning. So the researcher's orientation in further research needs to be to conduct research on social media in collaborative learning in PAI subjects; 2) RQ2: Network Theme in Social Media Research and Collaborative Learning in PAI Learning, namely the distribution of publication of articles related to